The North-South Gas Corridor in the Context of Poland’s Gas Transmission System—A Perfect Opportunity to Diversify Gas Resources - Wiktor Hebda (MDPI AG, 2021)
The energy sector in Poland is currently calling for dynamic redevelopment and cleaner energy. This country is world famous for its high level of coal production, from which it does not want to retreat in the next two decades. For this reason, it is safer to gradually reduce the use of coal while increasing the consumption of gas and simultaneously developing green energy. However, the Polish gas sector is still dependent on Russian gas supplied through the Yamal gas pipeline. Taking into consideration Polish geopolitics, this state of affairs poses a huge challenge and a threat to Poland’s energy security. That is why the concept of the North-South Gas Corridor was introduced. It is intended to be a network of gas pipelines that connect the countries of Central and South Europe to two gas terminals (in Poland and Croatia), which will supply gas from a chosen source. This article presents the current condition of the gas sector in Poland. It focuses on the North-South Gas Corridor project and its impact on the energy security of Poland. An analysis of documents and field research shows that the North-South Gas Corridor provides Poland with an opportunity to diversify the sources and directions of gas supply over the next few years.